Distribution of microglia/immune cells in the brain of adult zebrafish in homeostatic and regenerative conditions: Focus on oxidative stress during brain repair. Issue 2 (25th October 2022) - Narra, Sai Sandhya; Rondeau, Philippe; Fernezelian, Danielle; Gence, Laura; Ghaddar, Batoul; Bourdon, Emmanuel; Lefebvre d'Hellencourt, Christian; Rastegar, Sepand; Diotel, Nicolas
Abstract: Microglia are macrophage‐like cells exerting determinant roles in neuroinflammatory and oxidative stress processes during brain regeneration. We used zebrafish as a model of brain plasticity and repair. First, by performing L‐plastin (Lcp1) immunohistochemistry and using transgenic Tg( mpeg1.1:GFP ) or Tg( mpeg1.1:mCherry ) fish, we analyzed the distribution of microglia/immune cells in the whole brain. Specific regional differences were evidenced in terms of microglia/immune cell density and morphology (elongated, branched, highly branched, and amoeboid). Taking advantage of Tg( fli:GFP ) and Tg( GFAP::GFP) enabling the detection of endothelial cells and neural stem cells (NSCs), we highlighted the association of elongated microglia/immune cells with blood vessels and rounded/amoeboid microglia with NSCs. Second, after telencephalic injury, we showed that L‐plastin cells were still abundantly present at 5 days post‐lesion (dpl) and were associated with regenerative neurogenesis. Finally, RNA‐sequencing analysis from injured telencephalon (5 dpl) confirmed the upregulation of microglia/immune cell markers and highlighted a significant increase of genes involved in oxidative stress (nox2, nrf2a, and gsr) . The analysis of antioxidant activities at 5 dpl also revealed an upregulation of superoxide dismutase and persistent H2 O2 generation in the injured telencephalon. Also, microglia/immune cells were shown to be a source of oxidative stress at 5 dpl. Overall, our data provide a better characterization of microglia/immune cell distribution in the healthy zebrafish brain, highlighting some evolutionarily conserved features with mammals. They also emphasize that 5 days after injury, microglia/immune cells are still activated and are associated to a persistent redox imbalance. Together, these data raise the question of the role of oxidative stress in regenerative neurogenesis in zebrafish.